"You're So Hot!": A content analysis of sexual harassment among hotel employees - Alagappar, P.N.; Lean, M.L.; David, M.K.; Ishak, Z.; Ngeow, Y.M. (2011)
A major issue facing the hospitality industry is that of sexual harassment and the explosion in the number of sexual harassment lawsuits being filed. In recent years. there has been an increasing amount of empirical research on sexual harassment in Malaysia and the findings indicate that between 35 percent and 53 percent of women have experienced sexual harassment at work. Organizational culture represents the norms of appropriate behavior and values held by members of a particular organization. The hospitality industry is particularly vulnerable to sexual harassment problems. Thus. it is important to determine the understanding of sexual harassment among Malaysian working women and to determine if they recognize the behaviors or act that constitute sexual harassment. Since there are no constitutional guidelines on sexual harassment in Malaysia, sexual harassment as a term can lead itself to widely differing explanations.